Yield Tables for Eucalyptus Hybrid (Plantation) for Various Levels of Stocking - Sharma, R. P. (Indian Forester, 1978)
Yield tables for Eucalyptus hybrid (Plantation) have been presented by one year age classes from 4 through 14 years for different stockings and three site index classes. Tables for crop characters such as d.b.h., height, basal area, total volume, C.A.I.& M.A.I. have been given.